2020
DOI: 10.1002/jcla.23235
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0001649 restrains gastric carcinoma growth and metastasis by downregulation of miR‐20a

Abstract: Gastric carcinoma (GC) is a familiar malignant carcinoma all over the world, which has high malignancy and poor prognosis. 1 Patients with early GC have a higher 5-year survival rate after surgery, but most patients are diagnosed with advanced GC at the time of admission. 2 With further research on the mechanism of GC, molecular therapy has become a hot spot in the field of GC. 3 Furthermore, a number of researches have shown that various genes are associated with GC. 4 Therefore, further research of the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Zhang et al 24 reported that circLARP4 can facilitate the expression of miR‐424‐5p target LATS1 and YAP by acting as a sponge of miR‐424‐5p. Another research displayed that hsa_circ_001649 restrained GC by sponging miR‐20a and then inactivated Wnt/β‐catenin and ERK pathways 25 . CiRS‐7 was also reported to be significantly upregulated in GC tissues and linked to poor survival 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 24 reported that circLARP4 can facilitate the expression of miR‐424‐5p target LATS1 and YAP by acting as a sponge of miR‐424‐5p. Another research displayed that hsa_circ_001649 restrained GC by sponging miR‐20a and then inactivated Wnt/β‐catenin and ERK pathways 25 . CiRS‐7 was also reported to be significantly upregulated in GC tissues and linked to poor survival 18 .…”
Section: Discussionmentioning
confidence: 99%
“…45 In lung cancer, circ-SHPRH plays an antitumor role by downregulating the expression of tumor-promoting miRNAs, miR-331-3p and miR-8-5p. 45 The miRNAs that can be absorbed by circ-SHPRH are shown in Figure 2.…”
Section: Circ-shprhmentioning
confidence: 99%
“… 44 For example, circ-SHPRH can inhibit the expression of Wnt3A and β-catenin by downregulating miR-20a, thereby inhibiting the proliferation, migration, and invasion of gastric cancer cells. 45 In lung cancer, circ-SHPRH plays an antitumor role by downregulating the expression of tumor-promoting miRNAs, miR-331-3p and miR-8-5p. 45 The miRNAs that can be absorbed by circ-SHPRH are shown in Figure 2 .…”
Section: Formation and Function Of Circ-shprhmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased miR-20a expression was shown to inhibit Wnt/β-catenin and RAS/RAF/ERK/MAPK signaling pathways. This, in turn, led to inhibition of growth, as well as the invasive and migratory properties of GC cells by in vitro experiments [33].…”
Section: Introductionmentioning
confidence: 99%